The Enforcement of the Notary Code of Ethics Based on the Law on Notary Positions in Theory and Practice - Tonglo, Abdi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
In accordance with the provisions of Act No. 2 of 2014 junto Act No. 30 of 2004, the enforcement of the Notary Code of Ethics is carried out by the government through the Notary Supervisory Council and notary professional organizations (INI). This has an impact on the existence of two institutions that are authorized to enforce the Notary Code of Ethics. The affirmation of the authority of the two institutions in question needs to be examined normatively and empirically. This study uses a juridical-empirical research type. This method is carried out through a literature study that examines secondary data, in the form of books, journals, and laws and regulations complemented by data collection and interviews with the Kendari City Notary Regional Supervisory Board and the Kendari City Indonesian Notary Association Regional Board. In practice, the Enforcement of the Notary Code of Ethics in Kendari City is mostly carried out by the Notary Supervisory Board. Indonesian Notary Association through the Notary Honorary Council is more on resolving complaints of internal notary violations.Keywords: Enforcement, Ethics; Notary.1. Introduction